The harbingers of breaching of the Abbasid Caliphate’s symbolism during the dominance of foreign powers on the caliphate. Comparative Critical overview (Zien Journal of Social Sciences and Humanities, 2023)
This study explores a significant phenomenon characterized by the harbingers of the symbolic authority of the Abbasid Caliphate during periods of foreign dominance. It provides an analysis, critique, and comparison of the strategies employed by the Turkish, Buyids, and Seljuks, which contributed to the weakening of the caliphate. Throughout these three historical periods, the Abbasid Caliphate experienced profound vulnerability, as external forces marginalized their political significance, reducing their role to one of religious symbolism. Furthermore, the caliphs lost the sanctity and influence they once held during the prosperous and powerful days of Islamic rule, as this symbolic authority became shared with Seljuk officials. This research project seeks to bridge this gap by shedding light on the impact of foreign powers on Islamic authority within the context of the Abbasid caliphate during the Turkish, Buyids, and Seljuk eras.